(untitled) (Lafia Journal of Scientific and Industrial Research, 2023)
The techniques commonly used in estimating the extent of acetylation are based on the principle of substituting hydroxyl groups with acetyl groups. In this study, three lignocellulosic materials were modified using a solvent-free method of acetylation with NBS (N – bromosuccinimide) as a catalyst. The extent of modification of these materials was estimated using three techniques – weight percent gain (WPG), extent of acetylation (R), and degree of substitution (DS). Six (6) factors were considered in the acetylation of the lignocellulosic materials. Equality of variance – covariance matrices of the techniques across the factors in all the materials were tested with Box’s M test. The performance and response of the techniques to variation of the factors studied were compared statistically using multivariate analysis (MANOVA) and Duncan multiple range test. MANOVA results showed no statistical difference in the response of the techniques towards variation of the factors studied in acetylating these materials. However, it also showed that there was a significant difference in the performance of the techniques used in estimating the extent of acetylation. Duncan multiple range test analysis indicated that WPG performed best in estimating the extent of acetylation. Thus, any of the techniques can be used to estimate the extent of acetylation satisfactorily.